Closed-Loop Insulin Delivery During Pregnancy in Women With Type 1 Diabetes. Issue 1 (March 2017) - Stewart, Z.A.; Wilinska, M.E.; Hartnell, S.; Temple, R.C.; Rayman, G.; Stanley, K.P.; Simmons, D.; Law, G.R.; Scott, E.M.; Hovorka, R.; Murphy, H.R.
Abstract : ( N Engl J Med. 2016;375:644–654) Closed-loop systems use a computer algorithm to adjust insulin-pump delivery in response to real-time continuous glucose measurements. Such systems may improve glycemic control in pregnant women with type 1 diabetes, who are increased risk of having negative fetal outcomes (congenital anomalies, still-birth, neonatal death, preterm delivery, and macrosomia).